DESIGN AN INTERNET OF THINGS-BASED BLOOD PRESSURE DETECTOR AND MONITOR - Akbar Sujiwa (BEST, 2023)
A sphygmomanometer is a tool for measuring blood pressure that is often used in the medical world. Sphygmomanometers are generally divided into 2, namely analog and digital sphygmomanometers. In modern times now Android smartphones have developed with various features that are already very sophisticated. Therefore, the author wants to design a digital sphygmomanometer that can measure blood pressure and provide a history of measurement results so that the public or patients candetermine the state of their blood pressure. To present this tool in this study, the author will try to integrate a digital blood pressure measuring instrument with IOT (internet of things) so that it becomes a blood pressure detection and monitoring tool. NodeMCU ESP8266 will be used to process data and also serve to connect to the internet. Then, the sensor used is the MPX5050GP sensor as a pressure measurement tool and then the pressure calculation data from the sensor is sent to Firebase which acts as a database, and later it can be accessed and monitored via a smartphone. Theresults of testing the sphygmomanometer tool that the researcher made and the testing of the comparative sphygmomanometer tool. On average, this test gets an accuracy difference of approximately 1%.